(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
In India, gold has long been regarded as a secure and dependable investment. New methods of purchasing gold have been made available by digital platforms in recent years, drawing in younger investors. The preferences of Gen-Z and older adults with regard to physical and digital gold are compared in this study. The study assesses their degree of awareness, the rationale behind selecting a specific form, and the influence of digitalization on investment choices. A questionnaire is used to gather primary data, which is then subjected to basic statistical analysis. The results show a distinct generational gap in gold investment decisions.